Cobalt–Cobalt Phosphide Nanoparticles@Nitrogen‐Phosphorus Doped Carbon/Graphene Derived from Cobalt Ions Adsorbed Saccharomycete Yeasts as an Efficient, Stable, and Large‐Current‐Density Electrode for Hydrogen Evolution Reactions. (12th August 2018) - Li, Guixiang; Yu, Jiayuan; Jia, Jin; Yang, Linjing; Zhao, Lili; Zhou, Weijia; Liu, Hong
Abstract: Development of electrocatalysts for hydrogen evolution reaction (HER) with low overpotential and robust stability remains as one of the most serious challenges for energy conversion. Herein, a serviceable and highly active HER electrocatalyst with multilevel porous structure (Co‐Co2 P nanoparticles@N, P doped carbon/reduced graphene oxides (Co‐Co2 P@NPC/rGO)) is synthesized by Saccharomycete cells as template to adsorb metal ions and graphene nanosheets as separating agent to prevent aggregation, which is composed of Co‐Co2 P nanoparticles with size of ≈104.7 nm embedded into carbonized Saccharomycete cells. The Saccharomycete cells provide not only carbon source to produce carbon shells, but also phosphorus source to prepare metal phosphides. In order to realize the practicability and permanent stability, the binderless and 3D electrodes composed of obtained Co‐Co2 P@NPC/rGO powder are constructed, which possess a low overpotential of 61.5 mV (achieve 10 mA cm −2 ) and the high current density with extraordinary catalytic stability (1000 mA cm −2 for 20 h) in 0.5m H2 SO4 . The preparation process is appropriate for synthesizing various metal or metal phosphide@carbon electrocatalysts. This work may provide a biological template method for rational design and fabrication of various metals or metal compounds@carbon 3D electrodes with promising applications in energy conversion and storage. Abstract : Cobalt‐cobalt phosphide nanoparticles embedded into nitrogen‐phosphorus doped carbonderived from Saccharomycetes, which provide carbon source to produce carbon shells and phosphorus source to prepare metal phosphides. The binderless and three‐dimensional electrodes possess a low overpotential of 61.5 mV (10 mA cm −2 ) and high current density with extraordinary catalytic stability (1000 mA cm −2 for 20 h).